Progress and perspective of trained immunity in teleost fish - Xinwei You; Jin Yang; Zhuang Wang; Qiyao Wang; Qin Liu; Yuanxing Zhang; Geert F. Wiegertjes; Dahai Yang (Reviews in Aquaculture, 2024)
Trained immunity defines the long‐term memory of innate immunity based on innate immune signalling, metabolic changes and epigenetic rewiring of trained innate immune cells, which are characterised by elevated inflammatory responses towards secondary stimuli. The activation of this non‐specific protection‐mediated memory in innate immune cells was identified to benefit host defences as well as play a detrimental role in inflammatory diseases. In this review, we focused on summing up the current progress about the inducers, effector cells, molecular mechanisms and protective effects of trained immunity that have been identified in both mammals and teleost fish, and discussing the future research and application of trained immunity in aquaculture. Revealing the mechanisms of trained immunity will not only provide a novel aspect for understanding the evolution of innate immune memory and their longer‐term protections, but also contribute to the rational design and evaluation of immunopotentiators, adjuvants and potential vaccines in aquaculture.